Dissolving microneedle with high molecular weight hyaluronic acid to improve skin wrinkles, dermal density and elasticity - Jang, M.; Baek, S.; Kang, G.; Yang, H.; Kim, S.; Jung, H. (International journal of cosmetic science, 2020)
Objectives Dissolving microneedle patches have been extensively studied in the field of cosmetics comparison with topical cosmetics focusing on the delivery of active ingredients. Nevertheless, the skin improvement effect of hyaluronic acid, which is mainly used as a backbone material for dissolving microneedle, was not analyzed. In this study, adenosine encapsulated high and low molecular weight hyaluronic acid dissolving microneedle patch (Ad‐HMN and Ad‐LMN) were evaluated with respect to skin wrinkling, dermal density, elasticity, and safety in a clinical test on the crow’s feet area. Methods Clinical efficacy and safety tests were performed for 12 weeks on twenty three female subjects with wrinkles around their eyes. The Ad‐HMN and Ad‐LMN patch were applied once every 3 days, in the evening, for 8 weeks to the designated crow’s feet area. Skin wrinkling, dermal density, and elasticity were measured by using PRIMOS® premium, Dermascan®C, Cutometer® MPA580, and Corneometer® CM 825, respectively. Results Both Ad‐HMN and Ad‐LMN groups showed statistically significant efficacy for almost all parameters. The Ad‐HMN patch had better effect on the mean depth of biggest wrinkles, maximum depth of biggest wrinkles, dermal density, and skin elasticity than the Ad‐LMN patch. No adverse effects were observed in either group during the test period. Conclusion In the clinical efficacy test of four skin‐improvement parameters, the Ad‐HMN patch showed the better effect than the Ad‐LMN patch with the similar adenosine dose. (a) Skin scanner images in crow’s feet region following consecutive application of the test material in the Ad‐HMN group (adenosine‐encapsulated high molecular weight HA DMNs) and the Ad‐LMN group (adenosine‐encapsulated low molecular weight HA DMNs) for 12 weeks. (b) Changes in the dermal density in crow’s feet region following consecutive application of the test material in the Ad‐HMN group and the Ad‐LMN group for 12 weeks. (c) Changes in the skin elasticity in crow’s feet region following consecutive application of the test material in the Ad‐HMN group and the Ad‐LMN group. Measurements were recorded before use, after 4 and 8 weeks of use and 2 weeks and 4 weeks after the use of the product was stopped. Both groups showed significant improvement in dermal density; these improvements were more enhanced in the Ad‐HMN group (n = 23, mean ± SEM; *P < 0.05, ***P < 0.001 compared with the values †P < 0.05 A vs. B groups based on before treatment). Résumé Objectifs Les patches à micro‐aiguilles dissolvantes ont fait l’objet d’études approfondies dans le domaine de la cosmétique en comparaison avec la cosmétique topique axée sur la diffusion de principes actifs. Cependant, l’effet améliorant de l’acide hyaluronique sur la peau, principalement utilisée comme matière de base pour la dissolution des micro‐aiguilles, n’a pas été analysé. Dans la présente étude, les patchs à micro‐éguilles dissolvant l’acide hyaluronique à poids moléculaire élevé et faible, encapsulé dans l’adénosine (Ad‐HMN et Ad‐LMN) ont été analysés par rapport à la formation des rides, la densité cutanée, l’élasticité et la sécurité d’emploi lors d’un test clinique sur la zone de pattes d’oie. Méthodes Des tests d’efficacité et de sécurité cliniques ont été réalisés pendant 12 semaines sur 23 sujets féminins ayant des rides autour des yeux. Les patchs Ad‐HMN et Ad‐LMN ont été appliqués une fois tous les trois jours, le soir, pendant huit semaines, dans la zone à pattes d’oie désignée. La formation de rides, la densité cutanée et l’élasticité ont été mesurées à l’aide de PRIMOS® premium, Dermascan® C, Cutometer® MPA580 et Corneometer® CM825, respectivement. Résultats Les deux groupes Ad‐HMN et Ad‐LMN ont présenté une efficacité statistiquement significative pour la quasi‐totalité des paramètres. Le patch Ad‐HMN a eu un meilleur effet sur la profondeur moyenne des rides les plus importantes, la profondeur maximale des rides les plus importantes, la densité cutanée et l’élasticité de la peau par rapport au patch Ad‐LMN. Aucun effet indésirable n’a été observé dans aucun des groupes pendant la période d’essai. Conclusion Lors du test d’efficacité clinique des quatre paramètres d’amélioration de la peau, le patch Ad‐HMN a eu un meilleur effet que le patch Ad‐LMN avec la dose d’adénosine similaire.